Orthosis for the lower extremity in an unstable knee joint at the phase of support - Pivovarov, Victor; Baev, Pavel; Vatolinskiy, Leonid; Boboshko, Ruslan (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The article describes the design of an orthosis for the knee joint — ankle joint — foot in conditions of instability of the knee joint at the support phase, as well as the design of a splint system and the principle of its operation. The developed design of the splint system, consisting of an orthosis for the knee joint — ankle joint — foot, makes it possible to move without any outside assistance for the patients, who are not able to lock (fix) their knee joint by themselves at the stage of support or have axial deformities of the lower extremity (valgus, varus). Biomechanical studies and clinical observations confirmed efficacy of the designed orthoses and advisability of their use in a complex of rehabilitative measures for the above kind of patients.